The Visualization of The Story of Panji in The Film of Panji Semirang as The Gambuh Dancer - I Wayan Budiarsa (Syntax Corporation, 2022)
The development of information, communication and technology, as the indicator of the modern era, has much been used by man to satisfy his daily needs. The digital technology, as one of the media, can be easily accessed anytime. The visualization of the story of Panji in the film entitled Panji Semirang as the Gambuh Dancer is the production of a film produced as the result of the collaboration between the Ministry Education and Culture through Balai Pelestarian Nilai Budaya (BPNB) of Bali Province and the Sanggar Seni Satrya Lelana, Batuan, Gianyar with the platform that Indonesiana is one of the creations using the digital technology. The visual audio record, which is commonly presented in the form of the classic performing art, has been transformed to the digital technological domain. The story presented is the time when Galuh Daha and her servant disguises as the Gambuh dancer â€œPanji Semirangâ€ when the wedding ceremony is organized for Panji and Galuh Ajeng. This strategy can make Panji aware that he is bewitched by Galuh Ajeng. Love is used as the theme of the film; in its dialogues the main characters speak the Old Javanese language and the servants spleak the Balinese language. The actor wears the traditional makeup and clothing. The pictures were taken at the area of Puseh Temple (a cultural heritage), Batuan Village, Gianyar, and at a traditional house located at Negara Village, Batuan, Gianyar. Satires and the other figurative expressions both in the Balinese language and Old Javanese language, as the verbal languages used by the characters, are used to express affirmation, comparison, contrast and allusion.